DISSOLVED ORGANIC FE(III) AND FE(II) COMPLEXES IN SALT MARSH POREWATERS - Luther G.W.; Shellenbarger P.A.; Brendel P.J. (My University, 1996)
Fe(III) and Fe(II) organic complexes were determined by spectroscopic methods after sephadex gel fractionation of salt marsh porewaters during June and July 1993. Fe(III), which is a significant anaerobic oxidant for sulfide mineral oxidation, was typically found in the 100-5000 molecular weight (MW) fraction indicative of humic and other organic complexing agents. Fe(II) was found in both the < 100 and the 100-5000 MW fractions with most of the Fe(II) found in the smaller MW class. Both forms of Fe precipitated with humic material when the pH of the porewaters became less than 3. There was a twofold decrease in the <5000 mw fractions, a ninefold increase in the> 5000 MW class, and a tenfold decrease in dissolved Fe concentration in sephadex gel fractions as the pH decreased from 5.0 to <3 for porewater. low ph values are attributed to sulfide mineral oxidation from severe drought conditions that caused significant dessication of the vegetated marsh. microelectrode measurements demonstrated o2 was not detected below 2 mm and that Fe(III) organic complexes should be significant oxidants in anoxic waters.